The Role of Pragmatics in Foreign Language Learning and Teaching - KEHAL, Meryem (Journal of Human Sciences, 2017)
Because learning English for communication is currently emphasized, the need for a re-consideration of the English learners’ needs becomes necessary. Learners need to become more adept at producing and comprehending the pragmatic intent of an utterance, on the principle that less context implies more language. This paper aims at bringing into discussion the need and the importance of incorporating pragmatics into English language teaching in the English Department at University Constantine, 1. It focuses on the idea that efficient English language teaching must integrate pragmatic factors and issues in order to obtain satisfactory results not only in the classrooms but, more importantly, when learners use the English language in real and authentic contexts.